Placing land cover pattern preferences on the map. Bridging methodological approaches of landscape preferences surveys and spatial pattern analysis - Carvalho-Ribeiro, Sónia (2014)
This paper presents an innovative methodological framework – Landscape Preferences Spatial Framework (LPSF) – which is able to translate landscape preferences, as expressed by various users, concerning possible land cover pattern compositions into land cover pattern preference maps. The innovative potential of the contribution lies in the exploration of a comprehensive methodical framework that facilitates the spatial representations of landscape demands by relevant user groups thus bridging the gap between landscape preference research and landscape planning. The LPSF developed here goes beyond the state of the art in translating local scale preference by people into regional scale planning settings. Throughout the paper the development and testing of the LPSF is described and explained. Although the paper focuses on the conceptual framework of the method, it also shows the results of its application in a case study.